Effects of Subtle Stimulus Strength on the Attentional Blink. (January 2013) - Joo, Sung Jun; Chong, Sang Chul
The attentional blink refers to a type of impairment in detecting a second target (T2) after detecting a first target (T1) in rapid serial visual presentation (RSVP). Until recently, the role of T1 and how it is related to limitations in postperceptual processing such as selective attention and memory have been intensively studied. Here, we focus on the role of T2 and investigate whether an unnoticeable difference in the stimulus strength of T2, as indexed by the contrast of stimuli, can still influence this postperceptual process. We found that T2 performance was modulated by subtle T2 strength differences, although the T2 strength difference was not perceptually noticeable within the RSVP stream. These results suggest that T2 strength is important in the postperceptual stages of T2 processing-consolidation.